Pendampingan Pembuatan Buku Saku Panduan Wisata Bilingual Indonesia–Mandarin oleh Mahasiswa Prodi Pendidikan Bahasa Mandarin Universitas Negeri Makassar - As’ary, Muawwal Al; Wahyuni, Sry; Samad, Ita Sarmita; Noni, Nur Nasharuddin; Ernawati, Ernawati (Universitas Negeri Makassar, 2025)
Abstract. This project aims to design a digital pocketbook containing essential vocabulary and practical phrases in Mandarin to assist Indonesian tourists and tourism workers in effectively communicating during their stay in China. The digital pocketbook features categorized expressions tailored to common travel situations, such as interactions at airports, using public transportation, visiting tourist destinations, or ordering food at restaurants. Each phrase is presented in both Mandarin and Indonesian, making it accessible and practical for users regardless of their language proficiency. Additionally, the pocketbook is enriched with visual elements, such as icons and illustrations, to support non-verbal communication and facilitate easier understanding in real-life interactions. Through this participation, students gain hands-on experience in language application, digital media design, and intercultural communication practices. The integration of language education with real-world application not only supports community empowerment in tourism but also enhances the students' academic and professional development in linguistics and digital literacy. Ultimately, this project contributes to fostering cross-cultural communication and improving the quality of tourism experiences for Indonesian travelers in China.Keywords: Digital pocketbook, Mandarin language, Indonesian tourists, cross-cultural communication, Chinese tourism, community service